Effects of Thermal and Humidity Aging on the Interfacial Adhesion of Polyketone Fiber Reinforced Natural Rubber Composites - Han Ki Lee; Dae Sik Kim; Jong Sung Won; Da Young Jin; Hyun Jae Lee; Seung Goo Lee (Advances in Materials Science and Engineering)
Polyketone fiber is considered as a reinforcement of the mechanical rubber goods (MRG) such as tires, automobile hoses, and belts because of its high strength and modulus. In order to apply it to those purposes, the high adhesion of fiber/rubber interface and good sustainability to aging conditions are very important. In this study, polyketone fiber reinforced natural rubber composites were prepared and they were subjected to thermal and humidity aging, to assess the changes of the interfacial adhesion and material properties. Also, the effect of adhesive primer treatment, based on the resorcinol formaldehyde resin and latex (RFL), of polyketone fiber for high interfacial adhesion was evaluated. Morphological and property changes of the rubber composites were analyzed by using various instrumental analyses. As a result, the rubber composite was aged largely by thermal aging at high temperature rather than humidity aging condition. Interfacial adhesion of the polyketone/NR composites was improved by the primer treatment and its effect was maintained in aging conditions.